2000
DOI: 10.1001/jama.284.15.1948
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Misoprostol Administered 1, 2, or 3 Days After Mifepristone for Early Medical Abortion

Abstract: Our results suggest that vaginal misoprostol, 800 microg, can be used from 1 to 3 days after mifepristone, 200 mg, for early medical abortion, and need not be administered strictly 48 hours after mifepristone. JAMA. 2000;284:1948-1953.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
106
3
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(120 citation statements)
references
References 12 publications
8
106
3
3
Order By: Relevance
“…As previous studies and even in our study 61% of women having retained poc aborted spontaneously after 2 nd dose avoiding surgical intervention. 12 The safety of medical abortion with vaginal administration of misoprostol at home has been consistent with other studies. 10,11 Patients who had no or scanty bleeding or persistent bleeding more than 14 days are advised to follow up in the hospital.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As previous studies and even in our study 61% of women having retained poc aborted spontaneously after 2 nd dose avoiding surgical intervention. 12 The safety of medical abortion with vaginal administration of misoprostol at home has been consistent with other studies. 10,11 Patients who had no or scanty bleeding or persistent bleeding more than 14 days are advised to follow up in the hospital.…”
Section: Discussionsupporting
confidence: 88%
“…The overall success rate was slightly lower than the internationally reported 89% -97%. 10,[11][12][13][14] The reason for this is we rely heavily on USG to determine complete abortion. The studies showing higher success rate has waited for one month or even up to 40 days so that small debris will evacuate naturally and do not require surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the data collected on 16 000 women who had been treated with 600 mg of mifepristone followed by a prostaglandin analogue 24-72 hours later suggested that the efficacy was highest if the interval was 48 hours. 9 Different time intervals between mifepristone and misoprostol have also been tested 10 or both drugs have been administered simultaneously, 11 repeating the dose of misoprostol if abortion was not complete. When misoprostol was not repeated, complete abortion rates seem to be significantly lower with shorter intervals.…”
Section: Introductionmentioning
confidence: 99%
“…The use of mifepristone between 9 and 13 weeks gestation is equally effective as a cervical primer [31]. Animal studies showed that mifepristone induces collagen remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…The prostaglandin analogue, misoprostol, is more commonly used in this indication because it is cheaper and largely available. Nevertheless, bleeding and abdominal pain are decreased with mifepristone compared with misoprostol [31,33].…”
Section: Introductionmentioning
confidence: 99%